Suitability of carbon fiber-reinforced polymers as power cable cores: Galvanic corrosion and thermal stability evaluation. (January 2015) - Santos, T.F.A.; Vasconcelos, G.C.; de Souza, W.A.; Costa, M.L.; Botelho, E.C.
Graphical abstract: Highlights: Aluminum conductor composite core was proposed to replace steel-reinforced cables. Galvanic corrosion was stimulated by direct contact of raw carbon fibers and aluminum. Epoxy coating with fibers braiding showed to be suitable to prevent galvanic currents. Epoxy coating achieved glass transition temperature as high as 200 °C after post cure. Abstract: The increasing demand for electrical energy and the difficulties involved in installing new transmission lines presents a global challenge. Transmission line cables need to conduct more current, which creates the problem of excessive cable sag and limits the distance between towers. Therefore, it is necessary to develop new cables that have low thermal expansion coefficients, low densities, and high resistance to mechanical stress and corrosion. Continuous fiber-reinforced polymers are now widely used in many industries, including electrical utilities, and provide properties that are superior to those of traditional ACSR (aluminum conductor steel reinforced) cables. Although composite core cables show good performance in terms of corrosion, the contact of carbon fibers with aluminum promotes galvanic corrosion, which compromises mechanical performance. In this work, three different fiber coatings were tested (phenol formaldehyde resin, epoxy-based resin, and epoxy resin with polyester braiding), with measurements of the galvanic current. The use of epoxy resin combined with polyester braiding provided the best inhibition of galvanic corrosion. Investigation of thermal stability revealed that use of phenol formaldehyde resin resulted in a higher glass transition temperature. On the other hand, a post-cure process applied to epoxy-based resin enabled it to achieve glass transition temperatures of up to 200 °C.